Comparison of Air Pressure Control Between Discrete and PID Control Applied in the Calibration Process in Blood Pressure Meter - Harisha Avin Nurcahyana; Tri Bowo Indrato; Triana Rahmawati; Wahyu Caesarendra (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
In performing the calibration of the sphygmomanometer, the officer needs to first reset the installation and pump the bulb slowly until it reaches the set point in accordance with the calibration settings where this does not provide convenience to the calibration officer. So the author wants to do research on making additional devices to support DPM calibration instruments that have been commercialized to speed up the pump process in Sphygmomanometer calibration. The purpose of this research is to make an Automatic Pump module with PID control to analyze the stability of the pressure achievement in accordance with the set point when using the smoothing program or not. This study used set points of 50, 100, 150, 200, and 250 mmHg. Data retrieval was carried out within 260 seconds at each set point at the Campus of the Department of Electrical Engineering Poltekkes Kemenkes Surabaya. The results of this study indicate that the tool testing using the smoothing program experienced small oscillations compared to the program without smoothing. The data obtained are at setting 50 the average overshoot is 54 and the average undershoot is 49; at setting 100 the average overshoot is 109 and the average undershoot is 99; at setting 150 the average overshoot is 156 and the average undershoot is 149; at setting 200 the average overshoot is 206 and the average undershoot is 196; at setting 250 the average overshoot is 253 and the average undershoot is 247. The importance of this device was made in order to make it easier and faster for the calibration officer to calibrate the Sphygmomanometer.